2021
DOI: 10.1021/acs.analchem.1c01248
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Intelligent Imaging of Nanoscale Reactivity and Topography by Scanning Electrochemical Microscopy

Abstract: Scanning electrochemical microscopy (SECM) enables reactivity and topography imaging of single nanostructures in the electrolyte solution. The in situ reactivity and topography, however, are convoluted in the real-time image, thus requiring another imaging method for subsequent deconvolution. Herein, we develop an intelligent mode of nanoscale SECM to simultaneously obtain separate reactivity and topography images of non-flat substrates with reactive and inert regions. Specifically, an ∼0.5 μm-diameter Pt tip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A sharp, flat, and damage-free tip was positioned at a distance, d , of ∼50 nm from the atomically flat HOPG surface, as established previously. , Specifically, an ∼1 μm-diameter Pt tip was surrounded by a thin glass sheath with an outer diameter of ∼2 μm and flattened by focused-ion-beam milling (Figure S2A). , The tip was protected from electrostatic damage, as confirmed after SECM experiments (Figure S2B). The tip–HOPG distance was controlled precisely and quickly by measuring an approach curve in the intelligent mode , to prevent the tip–substrate contact (Figure S3) and minimize the fouling of the HOPG surface by residual contaminants in redox molecules, respectively.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…A sharp, flat, and damage-free tip was positioned at a distance, d , of ∼50 nm from the atomically flat HOPG surface, as established previously. , Specifically, an ∼1 μm-diameter Pt tip was surrounded by a thin glass sheath with an outer diameter of ∼2 μm and flattened by focused-ion-beam milling (Figure S2A). , The tip was protected from electrostatic damage, as confirmed after SECM experiments (Figure S2B). The tip–HOPG distance was controlled precisely and quickly by measuring an approach curve in the intelligent mode , to prevent the tip–substrate contact (Figure S3) and minimize the fouling of the HOPG surface by residual contaminants in redox molecules, respectively.…”
Section: Methodsmentioning
confidence: 59%
“…33,34 The tip was protected from electrostatic damage, 35−37 as confirmed after SECM experiments (Figure S2B). The tip−HOPG distance was controlled precisely and quickly by measuring an approach curve in the intelligent mode 37,38 to prevent the tip−substrate contact (Figure S3) and minimize the fouling of the HOPG surface by residual contaminants in redox molecules, 28 respectively. The tip− substrate nanogap was maintained by minimizing the thermal drift of the tip by using a homebuilt isothermal chamber.…”
Section: T H Imentioning
confidence: 99%
“…The current fluctuation in the upper right corner of the SECM image was attributed to the varied surface roughness of the polycrystalline gold substrate. [ 22–24 ] In Figure 3a, under acidic conditions, the tip current was between 1.79 and 1.38 nA, which was obviously larger than the limiting steady‐state diffusion current (1.2 nA). Because the amount of carboxylate that dissociated from the carboxyl groups under acidic conditions was negligible, electron tunneling occurred directly on the MPA SAM surface.…”
Section: Resultsmentioning
confidence: 98%
“…They found that the tunnelling current shows an exponential dependence on tip−substrate distance at slow tip approach rates. Recently, Jantz et al 120 developed the intelligent mode of SECM to simultaneously obtain separate reactivity and topography images of nonflat substrates with both reactive and inert regions. This method does not need specialized hardware, including a bifunctional probe.…”
Section: Nanopipette Applicationsmentioning
confidence: 99%